Flexible-Tip Laparo-Endoscopic Surgery: A Bridge to Single Port Appendicectomy in Children - Zani, A.; Ade-Ajayi, N. (European Journal of Pediatric Surgery, 2011)
Single port surgery (SPS) has been demonstrated to have some advantages over conventional laparoscopy. However, currently available port sizes may limit the application in younger children or those with a small umbilicus. Moreover, the consultant learning curve required to master single port surgery may have a negative impact on surgical training. We report the first series of children who were treated with a reduced incision technique for appendicectomy using flexible-tip laparo-endoscopic surgery (FLES).FLES was set up using one 11-mm and 2×5-mm bladeless ports (Ethicon XCEL™) via umbilical and low left iliac fossa incisions. A 10-mm flexible-tip laparo-endoscope was utilized. Tip angulation ensured visibility while minimising instrument clashing. A database of children undergoing FLES was kept prospectively. Demographic and peri-operative information and complications were recorded. Data are presented as medians with ranges.Between March and June 2010, 5 children (4 females) aged 9 (4–13) years underwent FLES for right iliac fossa pain. 2 procedures were performed by the admitting consultant, 3 by a supervised inexperienced laparoscopic trainee. 4 children had acute appendicitis including 1 with an inflammatory mass. Another had a haemorrhagic ovarian cyst. Appendicectomy was performed in all. The duration of surgery was 104 (93–130) min, and postoperative hospital stay was 2 (1–6) days. At 7 (5–8) months’ follow-up no complications have been recorded. At follow-up, the cosmetic results were judged to be excellent in all by the children, their parents and the reviewing surgeon.FLES is an alternative to standard laparoscopy and SPS in children, and be performed effectively and safely by junior trainees. Cosmetic results are excellent. It may represent a bridge technology, particularly for younger children, until single port products and techniques more suitable for appendicectomy in this age group are available. Finally, flexible-tip technology may play a useful role as SPS evolves.
Keywords: laparoscopy; flexible-tip; single port surgery; paediatric; appendicectomy